Self-configuration and self-optimization process with taguchi method in hybrid optical wireless network - Adam Wong Yoon Khang; Arnidza Ramli; Shamsul J. Elias; J. Pusppanathan; Jamil Abedalrahim Jamil Alsayaydeh; Fatin Hamimi Mustafa; Win Adiyansyah Indra; Johar Akbar Mohamat Gani (Institute of Advanced Engineering and Science, 2020)
In this paper, an alternative improvement is proposed which is the adaptive wireless access networks-based optical backhaul convergence that will greatly promote to use the existing resource of MANET (mobile ad hoc network). However, these characteristics itself acts as a drawback to the MANET applications such as the random distribution of nodes and continuously changing topology. MiNiTab statistical software was used to model the effect of the parameter variation to predict the field quality through the design of experiments while OMNeT++ network simulation was created to visualize the effect of QoS performance study in response with varying speed scenario. The result shows that the proposed ESCMDR scheme can obtain robustness and outperformed compared to the non-Taguchi previous study when it is used in random waypoint mobility model in any speed of sources. The work is based on packet delivery ratio (PDR) and packet loss Probability (PLP) metric under the varying speed scenario. It results in better QoS network PDR of 28.9% improvement, with 83.56% improvement on average PLP. The paper shows that the MANET QoS performance constrained can be addressed with the self-configured data rate of integrated optimization with taguchi method on AODV-UU (Adhoc On demand distance vector-uppsala university) routing technique.